Microsoft SharePoint 2013 - Cawood, Stephen (New York McGraw-Hill Education, 2013)
Explains how to get the most out of this powerful business collaboration platform. Learn how to use document management functions, wikis, taxonomy, blogs, My Sites, web parts, and more. Take full advantage of the content management, enterprise search, collaboration, and information-sharing capabilities of SharePoint 2010 with help from this practical guide
Introduction and SharePoint history -- SharePoint concepts -- Working with documents -- Collaboration -- Tagging and taxonomy -- Publishing sites -- Personal sites and personalization -- Web parts and app parts -- Customization -- Using SharePoint with client applications -- Introduction to SharePoint administration -- Introduction to SharePoint development -- Template reference for apps, pages, and sites
Includes index
Includes bibliographical references and index
1 2
Keywords: Microsoft Office; Microsoft Office; Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); Business -- Computer programs; Business -- Computer programs; Intranets (Computer networks); Intranets (Computer networks)